Indian Economy@75: Achievements, Gaps and Aspirations for the Indian Centenary. Issue 3 (September 2022) - Kumar, Nagesh
One of the largest and richest economies of the world in much of the human history, India emerged from the colonial rule in 1947, as one of the poorest countries. Much has been achieved over the past 75 years in both economic and social terms. However, many challenges remain that need to be addressed over the next quarter century. In this essay, an overview of the key achievements and the gaps in India's socio-economic development is presented, in the context 'Azadi ka Amrit Mahotsav', celebrating India's 75th year of Independence. It also summarises aspirations for the Indian Centenary that will be celebrated in 2047 and a vision of India's global leadership, not only in economic terms but also in terms of prosperity that is more inclusive, more sustainable and more resilient to enable her to celebrate the Centenary with a greater sense of national pride, achievement and fulfilment, becoming a role model for the developing world! JEL Codes: O53, O14, O11, O12